2011
DOI: 10.1111/j.1749-8198.2011.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Trends of Remote Sensing in Professional Urban Planning

Abstract: Remote sensing and remotely sensed data provide a spatial understanding of the complex physical characteristics, land uses, growth patterns, resource distributions, environmental pressures, technological changes, and socioeconomic needs of built environments. Despite the potential for remote sensing use in urban planning, a disconnect seems evident between academic research on remote sensing applications in an urban planning context and the actual adoption and use of remotely sensed technologies and data by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Two new sources of such data may come from remote sensing and citizen-generated maps and surveys. More-frequent and higherresolution imagery may help identify the type and quality of housing and physical infrastructure and track new construction (44)(45)(46). Working collaborations between local governments, communities, and civic organizations using new data collection, mapping, and reporting technologies will be essential to create detailed evidence that is accurate, verifiable, and expressive of residents' priorities (47,48).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Two new sources of such data may come from remote sensing and citizen-generated maps and surveys. More-frequent and higherresolution imagery may help identify the type and quality of housing and physical infrastructure and track new construction (44)(45)(46). Working collaborations between local governments, communities, and civic organizations using new data collection, mapping, and reporting technologies will be essential to create detailed evidence that is accurate, verifiable, and expressive of residents' priorities (47,48).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The rapid rate of growth and magnitude of the urbanization of populations, and land cover transitions from more natural to more built, requires greater data and information about urban areas and human settlement, including higher frequency of urban areas observations ( Hoalst-Pullen & Patterson, 2011a ; Zhu et al., 2019 ). These data demands are, in part, driven by broader motivations similar to the SDG aim of making sure “no one is left behind” ( United Nations - Economic, 2016 ), with a specific goal to expand the availability and accessibility of base data to help facilitate the planning, implementation, and assessment of programs and applications to achieve the 2030 SDGs ( Scott & Rajabifard, 2017 ; United Nations, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dramowicz et al (1993) have shown that 12% of planning programs worldwide have adopted GIS courses in their curriculum compared to 54% in geography. Despite increasing incorporation of GIS in the planning programs in the last 20 years (Hoalst-Pullen & Patterson, 2011), the progress has not been up to the mark with comparable disciplines. For example, recently Edwards and Bates (2011) found that only 5 (16%) planning programs, out of 30 surveyed, in the USA and Canada adopted GIS as a core planning method course at the post-graduate level.…”
Section: Introductionmentioning
confidence: 98%